2010
DOI: 10.1161/circimaging.109.923672
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Left Ventricular Hypertrophy and Geometry on Diagnostic Accuracy of Wall Motion and Perfusion Magnetic Resonance During Dobutamine Stress

Abstract: Background-The purpose of this study was to determine the influence of left ventricular (LV) hypertrophy and geometry on the diagnostic accuracy of wall motion and additional perfusion imaging during high-dose dobutamine/atropine stress magnetic resonance for the detection of coronary artery disease. Methods and Results-Combined dobutamine stress magnetic resonance (DSMR)-wall motion and DSMR-perfusion imaging was performed in a single session in 187 patients scheduled for invasive coronary angiography. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Hereby, increase in regional hypoenhancement during adenosine or dypiridamole stress (≥25% increase in hypoenhancement transmurality compared to baseline scans) in at least one myocardial segment, which persists for ≥5 consecutive image frames, is considered as indicative of inducible ischemia (Korosoglou et al, 2010b). Several studies also demonstrated the value of myocardial perfusion assessment during high dose dobutamine stress CMR for the detection of CAD, particularly in patients with left ventricular hypertrophy and concentric remodeling (Gebker et al, 2008, 2010). Recently, fully quantitative stress perfusion CMR was shown to exhibit higher precision for the detection of obstructive CAD (≥70% stenosis) compared to semi-quantitative and visual assessment (Mordini et al, 2014).…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…Hereby, increase in regional hypoenhancement during adenosine or dypiridamole stress (≥25% increase in hypoenhancement transmurality compared to baseline scans) in at least one myocardial segment, which persists for ≥5 consecutive image frames, is considered as indicative of inducible ischemia (Korosoglou et al, 2010b). Several studies also demonstrated the value of myocardial perfusion assessment during high dose dobutamine stress CMR for the detection of CAD, particularly in patients with left ventricular hypertrophy and concentric remodeling (Gebker et al, 2008, 2010). Recently, fully quantitative stress perfusion CMR was shown to exhibit higher precision for the detection of obstructive CAD (≥70% stenosis) compared to semi-quantitative and visual assessment (Mordini et al, 2014).…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…Potential influences of the LV geometry, in particular hypertrophy, have to be taken into account [2,24,31]. Adenosine stress perfusion magnetic resonance imaging is often used to detect hypoperfused areas and myocardial ischemia.…”
Section: How To Diagnose the Cardiac Phenotype Of Diabetic Cardiomyopmentioning
confidence: 99%
“…The imaging methodology has been described before [8]. In brief, cardiac standard geometries (three short axis views and a four-, two-and threechamber view) were acquired at rest and during each dobutamine stress level according to standard procedure [9].…”
Section: Mr Imagingmentioning
confidence: 99%
“…During maximum dobutamine-atropine stress additional perfusion imaging using identical geometry as the cine short axis views was performed using an intravenous bolus of 0.1 mmol/kg Gd-DTPA (Magnevist Ò , Bayer, Berlin, Germany), injection rate 4 ml/s, followed by a saline flush of 20 ml at the same rate. A single dose of Gd-DTPA was used for perfusion imaging in order to optimize for visual analysis [8]. A second injection of 0.1 mmol/kg Gd-DTPA was applied immediately after DSMR-perfusion without data acquisition to complete double dose for delayed enhancement imaging.…”
Section: Mr Imagingmentioning
confidence: 99%